PENGARUH PEMBERIAN INSENTIF, MOTIVASI DAN LINGKUNGAN KERJA DALAM KEPUASAN KERJA KARYAWAN PT. TELKOM AKSES WITEL SINGARAJA - Desi Anggreni, Gusti Komang; Satria, Gde Agung (Komunitas Manajemen Kompetitif, 2024)
The purpose of this study is to determine the influence of incentive provision, motivation, and work environment on employee job satisfaction at PT Telkom Akses Witel Singaraja. This research uses a quantitative approach. The data collection technique used in this study is in the form of questionnaires, where 52 employees were selected as respondents. This study uses multiple linear regression analysis. Based on the results of this study, it is explained that the incentive variable has a positive and significant effect on job satisfaction variable, the motivation variable has a positive and significant effect on job satisfaction variable, and the work environment variable has a positive and significant effect on employee job satisfaction variable.